Alcohol exposure alters the diversity and composition of oral microbiome - Zhao, Zirui; Li, Jiaxin; Liu, Juan; Zhang, Xiao; Qie, Yusen; Sun, Yutong; Liu, Na; Liu, Qing (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAlcohol exposure has been shown to have complex, and sometimes paradoxical, associations with various serious diseases. Currently, there is no knowledge about the effects of alcohol exposure on the dynamics of oral microbial communities.ObjectiveThe study aims to investigate the effects of chronic alcohol consumption on the diversity and composition dynamics of the rat oral microbiota using 16S rRNA gene amplicon sequencing.MethodsIn our study, there were 2 groups, including a control group (C group) and an alcohol group (A group), with 10 rats in every group. For ten weeks, rats in the A group were treated with alcohol intragastrically every day, whereas rats in the C group got water. After 10 weeks, serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were measured. Oral swabs were taken from both groups, and total DNA was extracted for high-throughput sequencing of the 16S rRNA gene.ResultsAccording to the results obtained from our study, significant differences were observed in the relative abundances of microbial communities. Alpha diversity measures were statistically significantly higher (P < 0.05) in the A group compared to the C group. At the genus level, alcohol exposure altered the relative abundance of several microbes, including increased relative abundance of unidentified_Chloroplast, Acinetobacter, Vibrio, Romboutsia, Pseudoalteromonas, Aeromonas, Ralstonia, Turicibacter, Shewanella, and Bacteroides. Conversely, Haemophilus and Streptococcus were significantly less abundant in the A group.ConclusionAlcohol exposure was associated with the diversity and composition of the oral microbiome. These findings contribute to our understanding of the potential role of oral bacteria in alcohol-related oral and systemic diseases, providing foundational work for future prevention and intervention studies.